Impact of P2P and free distribution on book sales - O'Leary, Brian (O'Reilly Media, 2009)
Book publishers have long used free content as part of their marketing and selling efforts, with the vast majority of free content distributed in printed form. Digital distribution of free material, either intentional or via unauthorized availability through peer-to-peer sites and other Web outlets, offers a fast and expansive connection to consumers, but content can also be copied and disseminated without publishers' control. Some publishers are torn between the efficiencies digital distribution provides and concerns over piracy and print-sale cannibalization. This research report is part of.